A self-defeating interpersonal style predicts depression over and above the Big 5 personality trait constructs - Breanna E Atkinson; Gabriela Lasky; Gregory J Boyle; Philip A Vernon (Archives of Depression and Anxiety - Peertechz Publications, 2019)
Three hundred and fifty-three adult participants completed self-report measures assessing depression, the putative "Big 5" personality factors, socially desirable responding, and a new scale intended to measure the propensity to engage in a self-defeating interpersonal style of behavior (the SELF-DISS; Atkinson & Vernon, 2018). Our goals were to see whether SELF-DISS scores would significantly predict depression and whether they would do so over and above the proposed "Big 5" trait constructs using online recruitment of participants from the general population at large. The recruitment method, although expeditious, necessarily resulted in the self-selection of participants, thereby raising the possibility that some sampling bias may have been incorporated into the study. Nevertheless, the results obtained clearly supported both predictions.